Perception, Knowledge, and Professional Behavior of Dentists about Silver Diamine Flouride: A Nationwide Survey - Abbas, Beenish; Aamer, Sidra; Anwar, Fizza Sahar; Farhan, Farah; Wajahat, Mehreen; Khurshid, Zohaib (European Journal of General Dentistry, 2021)
Objectives The aim of this study was to survey the educational experiences, knowledge, and attitude of dentists in Pakistan about the professional use of silver diamine fluoride (SDF). This study also aimed to determine if SDF educational experience at the undergraduate level can result in a more positive attitude and increased clinical usage of SDF.Materials and Methods This was a cross-sectional survey, conducted at multiple dental institutes across Pakistan using a pre-validated questionnaire to assess the knowledge, experience, and professional expertise of dentists regarding the use of SDF. The data were entered and analyzed using the SPSS (version 23.0) data management software by IBM.Results The results of this study were deemed significant in terms of achievement of the study aims. The majority of the responders, 178 (79.8%), reported online resources to be the main source of information about SDF treatment, whereas 103 (46.1%) responders gained information from a dental journal. A higher number of consultants were reported to be well educated regarding SDF treatment during their residency training as compared with demonstrators, house officers, and postgraduate trainees (p < 0.001). About 64 (28.7%) responders agreed that SDF is a better alternative treatment for children with behavioral issues, 74 (33.2%) agreed that it is a better treatment option for medically fragile patients, and 79 (35.4%) agreed that it can be used as an alternative for patients with dental anxiety. It was agreed by 82 (36.8%) responders that SDF is a good treatment option for patients who recently have received chemotherapy radiation therapy.Conclusion It is the need of time to put all educational efforts together to enhance knowledge regarding the use, advantages, and potential problems of SDF.
Keywords: dental technology; dentists; silver diamine fluoride